Comparison between Alināmeh and Shāhnāmeh - hasan haidari (Matn/Pizhūhī-i Adabī, 2012)
Alināmeh poetry book is the first religious epic written in Persian. Though Alināmeh is based on historical events, its author has selectively chosen the events and told the story of Jamal and Saffeyn wars in form of poetry by imitating Shāhnāmeh and mixing the truth and imagination. Both the epical language and imaginative form are imitated, but the author made some changes in the patterns used in Shāhnāmeh and made them suitable for a religious epic. Structural similarities between the two epics are belief in destiny, the array of troops, and fighting methods. As for differences, one can say that the roles are changed; the fortune-teller is changed from an astronomer to Imam or the epical hero; Demon is replaced with Satan, and also the type of exaggeration is changed. Moreover, impartiality can be observed in Shāhnāmeh as a national epic, while in the religious one which is Alināmeh, the author is partial. Alināmeh is a mixture of story, epic and history just like Shāhnāmeh.